Introduction: Cooperative Learning - Serrano, José-Manuel; Pons, Rosa-María (Anales de Psicología / Annals of Psychology, 2014)
The principal objective of this revision is the recognition of cooperative learning as a highly effective strategy for the accomplishment of the general goals in learning. The different investigations assessed validate the potential that a cooperative organization of the classroom could entail for academic achievement, self-esteem, interpersonal attraction or social support. The solidity of the existing research contributes to its external and internal validity and, thus, to conclude that the results are consistent and can be extrapolated to different cultures, ethnic groups or countries.